2000
DOI: 10.1021/la000406p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Micellar Electric Field on Electron-Transfer Processes (II):  A Study of the Ru(NH3)5pz2+ + Co(C2O4)33- Reaction in SDS Micellar Solution Containing NaCl

Abstract: Micellar effects on the oxidation reaction of [Ru(NH3)5pz]2+ with [Co(C2O4)3]3- in the presence of different NaCl concentrations were studied. Experimental results are discussed by using an approach based on the transition-state theory. It is shown that this approach used here is better than others based on the pseudophase model, which can also be used, because the former is able to give a clear meaning to the parameters of the model. Changes in the observed reactivity are explained by a change in the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…After this minimum, k obs increases as the CTACl concentration does. This variation of k obs is qualitatively similar to that observed for this reaction in the presence of micelles of SDS (see ref ).
2 Plot of k obs (s -1 ) of the process [Ru(NH 3 ) 5 pz] 2+ + [Co(C 2 O 4 ) 3 ] 3- versus CTACl concentration.
…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…After this minimum, k obs increases as the CTACl concentration does. This variation of k obs is qualitatively similar to that observed for this reaction in the presence of micelles of SDS (see ref ).
2 Plot of k obs (s -1 ) of the process [Ru(NH 3 ) 5 pz] 2+ + [Co(C 2 O 4 ) 3 ] 3- versus CTACl concentration.
…”
Section: Discussionsupporting
confidence: 88%
“…It should be mentioned that the reaction studied here has been previously studied in micellar solutions of sodium dodecyl sulfate (SDS) . The results obtained in this work will also be considered here for comparative purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, these are only estimated values because they depend on the location of the species which binds to the receptor, that is, on the α value. In any case, the values obtained assuming α = 1 are of the same order as those obtained previously by us in DNA and other charged receptors using other methods. , …”
Section: Discussionsupporting
confidence: 83%
“…According to the CMC model, the dependence of k obs as a function of bile salt concentrations (see Fig. ) can be written as truerightk obs =k aq +kmKMT1+KMT where T is equal to the total [bile salt] minus the CMC, k aq and k m are the rate constants in the aqueous (at the CMC) and in the micellar pseudophases, respectively, and K M is the binding equilibrium constant of the [Ru(NH 3 ) 5 pz] 2+ molecules to bile anion micelles. Application of Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The main conclusion was that the binding of ruthenium species to NaC aggregates can suitably be described by using a kinetic stepwise self‐association model. In addition, the comparison of the kinetic results for NaC aggregates and sodium dodecyl sulfate (SDS) micelles indicated that the aggregation feature of cholate ions did not lead to the formation of the Stern layer , which is a characteristic of the micellar alkyl systems.…”
Section: Introductionmentioning
confidence: 99%